Safeguarding good health of consumers: the opportunities and challenges of attaining quality compliance for processed cassava products in Africa - Abass, A.; Missanga, M.; Mosha, C.; Mukuka, I.; Ranaivoson, R.; Bah, A.J.; Fannah, S.; James, B.; Dziedzoave, N.T.; Waithaka, M.; Cromme, N. (International Society for Tropical Root Crops, 2012)
In Sub-Saharan Africa, cassava is mainly grown by smallholder farmers who also process the storage roots into traditional food products. However, improper processing techniques combined with climate variability aggravate risks of health hazards caused by residual toxic cyanogens and mycotoxin contamination of the food products. The introduction of improved processing technologies for the production of a diverse range of cassava-based food and industrial products has enhanced the crop's acceptance as a growing urban food item and industrial raw material. Standards for cassava and cassava products are required by regulatory institutions to assist food processors in producing good quality and safe products for consumption and industrial applications. This paper reports the on-going collaboration among national bureaus of standards, regional organizations, national and international research institutions such as IITA, and other value chain actors for developing specifications for cassava and cassava products and providing certification services to the producers. The paper highlights challenges of achieving conformity in national and regional standards in terms of factory hygiene, product quality and safety. The continuing efforts by IITA and partners, under the CFC-ESA and UPoCA projects, in assisting stakeholders alleviate these challenges are presented. Propositions are made for further supports from research, development and sub-regional organizations to address the current challenges of promoting standardization and quality compliance in cassava trade, commerce and industry in Sub-Saharan Africa.